Ties that bind: a critical discourse analysis of the coverage of the Millennium Development Goals in the Mail and Guardian - Marquis, Danika Ewen (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2009)
This study analysed the representation of the Millennium Development Goals (MDGs) in the Mail and Guardian from 2000 to 2007. It drew on perspectives from cultural studies, the constructionist approach to representation and the sociology of news production. Through the use of the quantitative and qualitative research methods, content analysis and critical discourse analysis, this study established first, that few significant changes have occurred within the newspaper's coverage of the MDGs during this period, and second, that the people most affected by the MDGs and affiliated programmes are seriously under-represented and that the manner of representation marginalises and subordinates them.
Keywords: Mail & Guardian; South African newspapers -- History -- 21st century; Journalism -- South Africa -- 21st century; Press -- South Africa -- 21st century; Developing countries -- Social conditions; Developing countries -- Economic conditions